2023
DOI: 10.1101/2023.10.03.559514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synovial macrophage diversity and activation of M-CSF signaling in post-traumatic osteoarthritis

Alexander J. Knights,
Easton C. Farrell,
Olivia M. Ellis
et al.

Abstract: ObjectiveSynovium is home to immune and stromal cell types that orchestrate inflammation following a joint injury; in particular, macrophages are central protagonists in this process. We sought to define the cellular and temporal dynamics of the synovial immune niche in a mouse model of post-traumatic osteoarthritis (PTOA), and to identify stromal-immune crosstalk mechanisms that coordinate macrophage function and phenotype.DesignWe induced PTOA in mice using a non-invasive tibial compression model of anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
1
0
0
Order By: Relevance
“…Csf1, also known as macrophage colony stimulating factor, is involved in the proliferation, survival, and differentiation of macrophages [42]. Similar to our results, Knights et al found SF-derived Csf1 signaling to function as a major crosstalk axis of macrophages activated by injury [43]. Collectively, synovial MSCs are considered to regulate their own activation by regulating their proliferation, polarity, and secretion via Ccl7, Spp1, and Csf1 signaling (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Csf1, also known as macrophage colony stimulating factor, is involved in the proliferation, survival, and differentiation of macrophages [42]. Similar to our results, Knights et al found SF-derived Csf1 signaling to function as a major crosstalk axis of macrophages activated by injury [43]. Collectively, synovial MSCs are considered to regulate their own activation by regulating their proliferation, polarity, and secretion via Ccl7, Spp1, and Csf1 signaling (Fig.…”
Section: Discussionsupporting
confidence: 89%